Choice of device to view video lectures: an analysis of two independent cohorts of first-year university students - Jesca Namuddu; Paul N. Watts (Association for Learning Technology, 2020)
Video lectures and mobile learning devices have become prominent, but little is known about device choices for watching video lectures. The setting for this study, a university that provided perpetual access to personal computers and free tablet devices to all first-year students, provided a unique opportunity to study device choice in a setting where both tablets and personal computers were perpetually available. Weekly video lectures on a first-year module were made from October to April in two independent cohorts of students. YouTube analytics were used to record data on device usage for video lecture views. Tablets were initially used for almost 70% of views. However, tablet usage declined throughout the academic year, and tablets were overtaken by personal computers as the preferred device in the second half of the academic year. Findings suggest that an initial preference for using tablets to view video lectures lasts only a few months.